Nigerian retail customers’ adoption of online banking in an Islamic Bank - Adewale, Abideen Adeyemi (Universal Publishers - Boca Raton, Florida, USA, 2014)
Purpose: The main purpose of this study is to present the pilot study result on the adoption of online banking by Nigerian retail customers of an Islamic Bank. Methodology: An extended Technology Acceptance Model was modified with awareness, trust and technology quality. Factor analysis and principal component analysis were conducted. A sample of sixty one Nigerian students of Linton University College and Nigerian staff of Nigerian High Commission in Malaysia were utilized in the study.Findings: The result revealed that reliability estimates for internal consistency Cronbach’s Alpha for all the thirty seven items used on seven construct ranged between 0.8 to 0.9 which is above 0.7. This indicates statistically acceptable internal consistency reliability. Originality/value: Despite significant contribution of online banking in enhancing globalisation of banking industry, less attention has been made on on the adoption of online banking in a developing nation like Nigeria. Indeed, most of the studies were conducted in developed countries. Thus, this study sought to explore the adoption of online banking in an Islamic bank that is from the retail customer’s perspective. The findings of this paper will be of importance to both financial industry and financial policy formation and future researchers in the field of online banking especially in Islamic banks.